COMPARATIVE STUDY ON THE EFFICACY OF TOPICAL METRONIDAZOLE, TOPICAL NITROGLYCERINE, AND TOPICAL DILTIAZEM IN THE MANAGEMENT OF CHRONIC ANAL FISSURE - GUPTA, PURSHOTAM DASS; TAUHEED, FAHAD; SARASWAT, ANURAG; P, Karthik (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Chronic anal fissure (CAF) is usually managed with surgical modalities but it imposes huge cost with recurrence rates. Hence, topical therapies are preferred is such cases which has a good patient acceptability rate. The present study aims to compare the topical metronidazole (MTZ), diltiazem (DTZ), and glyceryl trinitrate (GTN) in terms of healing rate and pain reduction in CAF patients. Methods: This was a randomized and prospective study conducted on 90 patients with CAF. The patients were grouped as follows (n=30), Group 1; 1% MTZ gel, Group 2; 0.2% Nitroglycerin ointment, and Group 3 (n=30): 2% DTZ ointment. The patients were evaluated at 2, 4, and 6 weeks for pain using visual analogue score (VAS) and healing rate. The results were compared and p<0.05 was considered as significant. Results: The VAS scores between the groups was found to be non-significant (p>0.05), however the VAS scores where markedly reduced within the group at 6 weeks. The healing rate was higher in MTZ group (90%) as compared to GTN (83.3%) and DTZ group (83.3%) but it was not significant. Regarding side effect, burning sensation was observed in MTZ and GTN, DTZ groups were devoid of side effects. Conclusion: The MTZ was more effective with good healing rate but with few side effects. Regarding the pain reduction, all the groups displayed equivocal effects. Thus topical MTZ is a suitable agent for the faster healing of CAF and thus avoids the requirement of surgical options.